Living a bare life: assembling the everyday of migrant domestic work in Cairo - Lilleby, Sabrina (AUC Knowledge Fountain, 2016)
This ethnographic study of work in Cairo argues that the laboring lives of migrant domestic workers in this locality are both similar and different to that of other spatial locations. Con- trary to the re-hashed representation in media, this text shows that migrant domestic workers in the Arabic speaking world are not what is often referred to as modern day slaves. Instead, I show how these workers shape and are shaped in accordance with a neoliberal govermentali- ty, through their techniques of managing their affects, bodies and actions. However, regard- less of the increasing focus on training subjects before entering the workplace, the market for domestic work in Cairo is not organized according to skill or merit, but rather according to nationality and gender. The pricing in this market is a reflection of a local and global hierar- chy where certain nationalities are marketed as skilled, docile and modern, while others are seen as human waste. Despite the constrictions this market creates and although they work without papers, workers’ rapid change of employment shows how these workers are not simply victims, but rather active subjects who practice unconventional forms of labor politics in navigating the micro politics of the everyday.